GREEN ECONOMY POLICY AS A WAY FOR SUSTAINABLE DEVELOPMENT - Mursid, Mansur Chadi; Prasetyo, Robby; Tamamudin, Tamamudin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research intends to find out green economy policies as a way to drive sustainable development. This study uses a systematic literature review method. Sources of research data come from journals and other literature. The findings in this literature review study conclude that this nation has several obstacles when trying to shift its economy to a more environmentally friendly direction. The efforts to quickly integrate environmental considerations into economic development should not be hampered. On the other hand, to assist efforts to support sustainable development, various obstacles must be overcome and international cooperation must be adopted. It is important to be careful not to diminish or deviate from sustainable development when dealing with a green economy in a way that is consistent with sustainable development ideas, values ​​and frameworks. The idea of ​​a green economy is also considered to include social, equity and development aspects and necessary global economic reforms.